The faith of the Old Testament a history - Schmidt, Werner H.; Sturdy, John (Philadelphia, PA Westminster, 1983)
Includes bibliographical references and index.
Published in German as Alttestamentlicher Glaube in seiner Geschichte (Neukirchener Studienbucher Band 6), 1968 ; fourth ed., 1982, Neukirchener Verlag des Erziehungsvereins GmbH, Neukirchen-Vluyn.